2013
DOI: 10.1186/1752-1505-7-25
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of HIV care during the 2007 post-election crisis in Kenya: a case study analyzing the response of the Academic Model Providing Access to Healthcare (AMPATH) program

Abstract: BackgroundWidespread violence followed the 2007 presidential elections in Kenya resulting in the deaths of a reported 1,133 people and the displacement of approximately 660,000 others. At the time of the crisis the United States Agency for International Development-Academic Model Providing Access to Healthcare (USAID-AMPATH) Partnership was operating 17 primary HIV clinics in western Kenya and treating 59,437 HIV positive patients (23,437 on antiretroviral therapy (ART)).MethodsThis case study examines AMPATH’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 19 publications
0
16
1
Order By: Relevance
“…The first, a pre-post study conducted in a camp setting during postelection violence in Kenya, evaluated a disaster response plan that included rapid information dissemination through the media, HIV outreach activities and a medical record system helping to track missed appointments among HIV-positive patients. 19 Using clinic attendance as the primary outcome, the study reported that the majority of clinics (60.0%, n=12) had more visits during their opening week, and that there was an overall increase in patient volume by 105% compared with the baseline. The number of unscheduled visits also increased from 27.2% pre-intervention to 42.4% three months after clinics were opened.…”
Section: Resultsmentioning
confidence: 99%
“…The first, a pre-post study conducted in a camp setting during postelection violence in Kenya, evaluated a disaster response plan that included rapid information dissemination through the media, HIV outreach activities and a medical record system helping to track missed appointments among HIV-positive patients. 19 Using clinic attendance as the primary outcome, the study reported that the majority of clinics (60.0%, n=12) had more visits during their opening week, and that there was an overall increase in patient volume by 105% compared with the baseline. The number of unscheduled visits also increased from 27.2% pre-intervention to 42.4% three months after clinics were opened.…”
Section: Resultsmentioning
confidence: 99%
“…41 The study by Kim et al 47 showed significant associations between recent STI symptoms and conflict-related sexual violence among IDP women compared to non-IDPs (aOR=3.9 and 4.2; P value <0.01 and =0.05, respectively). This indicated HIV care was of high priority in conflict settings and possible if planned effectively as shown in the study by Goodrich et al 42 which documented the experiences of offering HIV care in active conflict settings. Goodrich et al 42 advised for the inclusion of rapid case tracking, availability of resources, staff support and promotion of patient and community networks in HIV programs.…”
Section: Treatment and Essential Drugs Interventionsmentioning
confidence: 90%
“…This indicated HIV care was of high priority in conflict settings and possible if planned effectively as shown in the study by Goodrich et al 42 which documented the experiences of offering HIV care in active conflict settings. Goodrich et al 42 advised for the inclusion of rapid case tracking, availability of resources, staff support and promotion of patient and community networks in HIV programs. Findings from the TB and HIV studies illustrated the impact of conflict and migration on treatment uptake.…”
Section: Treatment and Essential Drugs Interventionsmentioning
confidence: 90%
See 1 more Smart Citation
“…There are promising data on the use of mobile phones and text reminders to support retention in HIV treatment (Horvath, Azman, Kennedy, & Rutherford, 2012) and on the use of mobile clinics and electronic medical records to support displaced HIV patients during emergencies (Goodrich et al, 2013). In the case of forced migrants, cloud-based health records accessed via mobile phone applications could mitigate the challenges of maintaining medical information and test results while in transit, although it will be important to identify and address issues of privacy and security.…”
Section: Available Services and Systems For Refugeesmentioning
confidence: 99%